Educational leadership in the knowledge age "from a formal position to a formative perception" the case of learning communities. Issue 1 (1st January 2019) - Ronen, Ilana Klima
ABSTRACT: The age of knowledge and social responsibility awareness raises the question about the role of the instructor as the leader of the educational process in a learning community. Based on qualitative analysis referred to students' reflective diary instructors' reports, and interviews – the study sheds light on three features of the leader of a learning community: individuality, involvement, and leadership – that emerged from three points of view (students as the instructed, students as peers-instructors, and the learning community instructors). The presence of these three features, which fit transformative leadership components, has contributed to the students during an educational process, while their absence has been an inhibiting factor. The findings are also relevant for teachers who face the challenges of their changing position in the learning-teaching process in a traditional class. Ways to respond to the challenge are based on: developing emotional awareness; encouraging self-reflective processes; and fostering transformative leadership.